Molecular Switches and Real-Time Ion Sensing in Pyridinium Circuits Via a Single-Molecule Stm-Break Junction - Cardenas-Jiron, G; Ponce-Hormazabal, I (Royal Society of Chemistry, 2025)
The functional electronic and spectro-electrochemical properties of two structural pyridinium isomers, Py_Down-BF4 and Py_Up-BF4, were studied at the single-molecule level using the STM-BJ technique. These isomers differ in the position of the redox-active pyridinium core. The aim was to identify the role of core s position in promoting reversible switching between electromers (redox isomers) in solution and at the gold-pyridinium-gold junction circuit. We measured the single-molecule conductance of each pyridinium isomer in various electrolyte environments using tetrabutylammonium salts (TBABF4, TBAPF6, TBABr, and TBACl). The choice of electrolytes played a crucial role in the histograms’ shapes—junction distribution, width, and peak position—which act as unique conductance fingerprints for each isomer. During STM-BJ measurements, a dynamic evolution in the conductance histograms was determined, particularly with the electrolytes TBAPF6 and TBABF4. This behavior was attributed to the real-time detection of interactions between the positively charged pyridinium core and the electrolyte anions within the gold-pyridinium-gold junction. The dynamic evolution in single-molecule conductance was rationalized by the Gibbs free energies (ΔG) for the anion-cation pairs obtained from density functional theory (DFT) calculations. Furthermore, the theoretical trend predicted by DFT combined with the Keldysh nonequilibrium Green s function (NEGF) formalism (DFT-NEGF) was consistent with the experimental results. © 2025 The Royal Society of Chemistry.